Why does the yield-curve slope predict recessions? - Luca Benzoni; Olena Chyruk; David Kelley (Federal Reserve Bank of Chicago, 2018)
Why is an inverted yield-curve slope such a powerful predictor of future recessions? We show that a decomposition of the yield curve slope into its expectations and risk premia components helps disentangle the channels that connect fluctuations in Treasury rates and the future state of the economy. In particular, a change in the yield curve slope due to a monetary policy easing, measured by the current real-interest rate level and its expected path, is associated with an increase in the probability of a future recession within the next year. In contrast, a decrease in risk premia is associated with either a higher or lower recession probability, depending on the source of the decline. In recent years, a decrease in the inflation risk premium slope has been accompanied by a heightened risk of recession, while a lower real-rate risk premium slope is a signal of diminished recession probabilities. This means that not all declines in the yield curve slope are bad news for the economy, and not all instances of steepening are good news either.
Keywords: G10; G12; E32; E37; E44; E52; 330; yield-curve slope; recession forecasts; monetary policy; bond risk premia; policy path